AB0181 Bone Marrow Derived Dendritic Cells Modified by Lentiviral-Mediated Relb Shrna Possess Tolerogenic Phenotype and Functions on Lupus Splenic Lymphocytes. (9th June 2015) - Wu, H.J.; Lo, Y.; Chan, A.; Mok, M.Y.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by high morbidity and mortality and remains challenging in treatment. Dendritic cells (DCs) have been shown to participate in the initiation and perpetuation of lupus pathogenesis. DCs that induce tolerogenicity appear as potential cell-based therapy in this condition. Objectives: In this study, we used lentiviral transduction of RelB-silencing shRNA to modify expression of RelB, a key transcription factor regulating DC maturation, in bone marrow-derived DCs from MRL/MpJ wild type mice and examined their tolerogenic properties using a lupus-prone MRL/lpr model. Methods: Lentiviral-mediated transduction of RelB-silencing shRNA or scrambled control shRNA were used to treat bone marrow derived DCs from MRL/MpJ mice. LPS-matured DCs, scrambled shRNA-modified DCs and RelB-modiified DCs were compared in terms of their tolerogenic properties. Results: We found that these MRL/MpJ RelB-modified DCs displayed semi-mature phenotype. These MRL/MpJ RelB-modified DCs were found to be low producer of IL-12p70, can induce hyporesponsiveness of splenic T cells from MRL/MpJ and lupus-prone MRL/lpr mice. Furthermore, they downregulated IFN-γ expression and induced IL-10 producing T cells in MRL/MpJ splenocytes, and attenuated IFN-γ and IL-17 expression in MRL/lpr splenic lymphocytes. Splenocytes primed by RelB-modified DCs demonstrated antigen-specific suppressive effect on allogeneic splenocytes. However, these CD4+ T cells with suppressive function were not found to express Foxp3. In the terms of chemokine receptor expression, there were no differences in the expression of CCR5, CCR7, and CXCR3 bewteen RelB- and scrambled control-modified DCs. Conclusions: RelB-modified DCs provide a method in the generation of tolerogenic DCs which may have potential therapeutic implications in the treatment of SLE. Disclosure of Interest: None declared